Identification of the sirohaem biosynthesis pathway in Staphylococcus aureus. (27th October 2019) - Videira, Marco A. M.; Lobo, Susana A. L.; Sousa, Filipa L.; Saraiva, Lígia M.
Abstract : Sirohaem is a modified tetrapyrrole and a key prosthetic group of several enzymes involved in nitrogen and sulfur metabolisms. This work shows that Staphylococcus aureus produces sirohaem through a pathway formed by three independent enzymes. Of the two putative sirohaem synthases encoded in the S. aureus genome and annotated as cysG, one is herein shown to be a uroporphyrinogen III methyltransferase that converts uroporphyrinogen III to precorrin‐2, and was renamed as UroM. The second cysG gene encodes a precorrin‐2 dehydrogenase that converts precorrin‐2 to sirohydrochlorin, and was designated as P2D. The last step was found to be performed by the gene nirR that, in fact, codes for a protein with sirohydrochlorin ferrochelatase activity, labelled as ShfC. Additionally, site‐directed mutagenesis studies of S. aureus ShfC revealed that residues H22 and H87, which are predicted by homology modelling to be located at the active site, control the ferrochelatase activity. Within bacteria, sirohaem synthesis may occur via one, two or three enzymes, and we propose to name the correspondent pathways as Types 1, 2 and 3, respectively. A phylogenetic analysis revealed that Type 1 is the most used pathway in Gammaproteobacteria and Streptomycetales, Type 2 predominates in Fibrobacteres and Vibrionales, and Type 3 predominates in Firmicutes of the Bacillales order. Altogether, we concluded that the current distribution of sirohaem pathways within bacteria, which changes at the genus or species level and within taxa, seems to be the result of evolutionary multiple fusion/fission events. Abstract : The enzyme co‐factor Sirohaem belongs to a key group of enzymes involved in nitrogen and sulfur metabolism. We show that Staphylococcus aureus produces sirohaem through a pathway formed by three independent enzymes: UroM, P2D and ShfC and that the distribution of sirohaem pathways in bacteria is linked to multiple evolutionary fusion or fission events.